2010
DOI: 10.1186/1476-9255-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of nanocrystalline silver-derived solutions in porcine contact dermatitis

Abstract: BackgroundNanocrystalline silver dressings have anti-inflammatory activity, unlike solutions containing Ag+ only, which may be due to dissolution of multiple silver species. These dressings can only be used to treat surfaces. Thus, silver-containing solutions with nanocrystalline silver properties could be valuable for treating hard-to-dress surfaces and inflammatory conditions of the lungs and bowels. This study tested nanocrystalline silver-derived solutions for anti-inflammatory activity.MethodsInflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 38 publications
0
71
1
2
Order By: Relevance
“…In vitro and in vivo experimental findings show that silver nanoparticles are effective at decreasing inflammation in peritoneal adhesions without significant toxic effects. 99 Nadworny et al 100 found that nanocrystalline silver-derived solutions appear to have anti-inflammatory and prohealing activity, predominantly with a starting pH of 9. Solutions has been generated differently having various silver species with varying concentrations, only some of which are anti-inflammatory.…”
Section: Silver Nanoparticles Suppress Both Local and Systemic Inflammentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo experimental findings show that silver nanoparticles are effective at decreasing inflammation in peritoneal adhesions without significant toxic effects. 99 Nadworny et al 100 found that nanocrystalline silver-derived solutions appear to have anti-inflammatory and prohealing activity, predominantly with a starting pH of 9. Solutions has been generated differently having various silver species with varying concentrations, only some of which are anti-inflammatory.…”
Section: Silver Nanoparticles Suppress Both Local and Systemic Inflammentioning
confidence: 99%
“…Solutions has been generated differently having various silver species with varying concentrations, only some of which are anti-inflammatory. 100 These Figure 5 Role of the Different Cytokines and Mediators at the Various Stages of Normal Wound Healing. ILGF-1, insulin-like growth factor 1; KGF, keratinocyte growth factor; PDGF, platelet-derived growth factor; VEGF, vascular endothelial growth factor; TGF-b 3, transforming growth factor beta 3; TGF-a, transforming growth factor alpha; HBEGF, heparin-binding epidermal growth factor; BFGF, basic fibroblast growth factor; AFGF, acidic fibroblast growth factor; TGF-b 1, 2, transforming growth factor beta 1, 2; TNF-a, tumor necrosis factor alpha; IL-1, -10, interleukin 1, 10; CSF-1, colony stimulating factor 1.…”
Section: Silver Nanoparticles Suppress Both Local and Systemic Inflammentioning
confidence: 99%
“…Silver nanoparticles are well known as one of the most universal antimicrobial substances in the field of biology and medicine due to their strong biocidal effect against microbial species, which has been used for centuries to prevent and treat various diseases, most notably infections. 14 Silver nanoparticles also reported to possess anti-fungal, 15 anti-inflammatory, 16 anti-viral, 17 anti-angiogenesis 18 and anti-platelet activity. 19 Recently, the development of silver nanoparticles is expanding.…”
Section: Introductionmentioning
confidence: 99%
“…The eco-friendly biosynthesis of silver nanoparticles using curcumin makes them superior wound healing product with enhanced biofilm activity [22][23][24]. Nano silver nitrate incorporated hybrid hAM bandage increases their manageability, provides the easier application to the burned area and creates a bactericidal effect, therefore reducing the risk of contamination and infection.…”
Section: Discussionmentioning
confidence: 99%